2012
DOI: 10.5194/acp-12-683-2012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among cirrus ice content, water vapor and temperature in the TTL as observed by CALIPSO and Aura/MLS

Abstract: Abstract. Water vapor in the tropical tropopause layer (TTL) has a local radiative cooling effect. As a source for ice in cirrus clouds, however, it can also indirectly produce infrared heating. Using NASA A-Train satellite measurements of CALIPSO and Aura/MLS we calculated the correlation of water vapor, ice water content and temperature in the TTL. We find that temperature strongly controls water vapor (correlation r = 0.94) and cirrus clouds at 100 hPa (r = −0.91). Moreover we observe that the cirrus season… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
(32 reference statements)
0
33
0
Order By: Relevance
“…Their results show that aerosols were predominantly moved poleward and show no signs of mixing back to their tropical origin in the lower stratosphere. Flury et al (2012) showed that total water (ice and vapor) is roughly constant in the tropical tropopause layer (TTL) at 100 hPa on seasonal time scales. However, the temperature determines the balance between ice in cirrus clouds and water vapour.…”
Section: T Flury Et Al: Variability Of the Brewer-dobson Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results show that aerosols were predominantly moved poleward and show no signs of mixing back to their tropical origin in the lower stratosphere. Flury et al (2012) showed that total water (ice and vapor) is roughly constant in the tropical tropopause layer (TTL) at 100 hPa on seasonal time scales. However, the temperature determines the balance between ice in cirrus clouds and water vapour.…”
Section: T Flury Et Al: Variability Of the Brewer-dobson Circulationmentioning
confidence: 99%
“…To compare our observations with the QBO we use the National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) reanalysis daily zonal wind data, which are retrieved on 17 pressure levels from 1000 hPa to 10 hPa. The method used to determine vertical and meridional speeds of the BDC is similar to the one introduced by Schoeberl et al (2008) and Flury et al (2012). We calculate the time lagged correlation in the H 2 O time series between two different levels.…”
Section: T Flury Et Al: Variability Of the Brewer-dobson Circulationmentioning
confidence: 99%
“…There is now evidence from several studies (Boehm and Verlinde, 2000;Immler et al, 2008;Fujiwara et al, 2009;Virts et al, 2010;Flury et al, 2012) that there is a correlation between cold anomalies in the TTL and cirrus clouds. From recent studies on cirrus clouds in the TTL using the lidar in space onboard CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation), the vertical motions in the regions of cirrus cloud occurrence were estimated (Virts et al, 2010).…”
Section: Large-scale Dynamicsmentioning
confidence: 99%
“…Here, we again use a lognormally distributed aerosol with modal diameter L m = 0.5 µm, a geometrical standard deviation of σ L = 1.4 and a total number concentration of N IN = 7 L −1 (see e.g. DeMott et al, 2003). The nucleation threshold is size-dependent, i.e.…”
Section: Ttl Ice Crystal Numbers From Heterogeneous and Homogeneous Nmentioning
confidence: 99%
“…Also, we characterize the impact of orbital sampling on derived lower-stratospheric tropical vertical velocities. These velocities are computed by correlating the lag of the water vapor "tape recorder" signal between adjacent levels (Niwano et al, 2003;Flury et al, 2012;Jiang et al, 2015). As such, they are likely an upper bound on the actual velocity (Schoeberl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%